Floral аbnormality in plants of the genera Сolchicum аnd Сrocus - GnatiukА. М.; Gritsenko, V. V.; Kushnir, N. V. (Regulatory Mechanisms in Biosystems, 2024)
The article presents the results of the study of abnormal flowers in representatives of the genera Colchicum L. and Crocus L. ex situ. The research was conducted in the M. M. Gryshko National Botanical Garden оf the National Academy of Science of Ukraine, Kyiv. Observations were made in 2019–2022 for 18 representatives of the genera Colchicum and Crocus. The research was carried out using the methods of comparative morphology and photofixation. Data on the phenology of plant flowering in Kyiv are presented. Photos and descriptions of 38 abnormal flowers are provided. A decrease or increase in the number of perianth segments, stamens, styloids (or stigmas) of gynoecium, floral virescence, and cuts on perianth segments was revealed. 26 types of abnormal flowers were found (16 for Colchicum species and 10 for Crocus species). Pearson correlation coefficients (R) for Colchicum flowers revealed negligible, and for Сrocus flowers – moderate and strong correlation. A comparative analysis of the normal and abnormal number of Colchicum flowers’ organs revealed that the widest range of percentage difference is characterized by the gynoecium. For Crocus, corolla are characterized by the widest percentage difference range. Among the studied taxa of the genus Colchicum, the largest number of abnormal flowers was recorded in C. bulbocodium Ker Gawl. and C. autumnale L. Among representatives of the genus Crocus – in C. heuffelianus Herb. The described flower anomalies are generally similar to those recorded by other researchers in natural conditions and in culture. For Colchicum and Crocus, the appearance of individual atypical flowers in inflorescences is characteristic and is caused by external factors, in particular, temperature changes, phytoplasma, damage to buds. Teratological changes in flowers occur as temporary developmental abnormalities and have no taxonomic or adaptive significance. In general, the resettlement of plants and their cultivation outside the natural range did not cause significant permanent changes in the flowers of Colchicum and Crocus.